2021
DOI: 10.1177/25158163211040072
|View full text |Cite
|
Sign up to set email alerts
|

Cranial suture headache: An extracranial head pain syndrome originating in the cranial sutures of the skull

Abstract: Objective: To define a new type of head pain syndrome termed “cranial suture headache” which is a localized headache originating along the cranial suture lines of the skull. Background: Well localized headaches maybe extracranial in origin. As trigeminal nociceptors are localized within the cranial sutures of the skull, these fibrous joints maybe the source of head pain for some patients. Methods: Case series. To diagnose cranial suture headache, the patient’s pain had to be localized to the skull and elicited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…It has been suggested that skull based trigeminal nociceptors can send signals centrally to the sensory trigeminal nucleus caudalis which could then produce a migraine like headache even though the generator is extracranial (10,12). Of note in the recently defined 'cranial suture headache' almost one-third of patients developed migrainous associated symptoms even though their syndrome was purely extracranial based (10,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that skull based trigeminal nociceptors can send signals centrally to the sensory trigeminal nucleus caudalis which could then produce a migraine like headache even though the generator is extracranial (10,12). Of note in the recently defined 'cranial suture headache' almost one-third of patients developed migrainous associated symptoms even though their syndrome was purely extracranial based (10,13).…”
Section: Discussionmentioning
confidence: 99%
“…Pain relief appeared to be from direct onabotulinumtoxinA administration into the craniotomy scar and transected/irritated cranial suture lines. One of the authors has recently defined cranial suture headache (not secondary to craniotomy) and the most dramatic pain relief came from onabotulinumtoxinA injected into the suture lines alone (13). There is also recent documentation that a suture only onabotulinumtoxinA injection paradigm was effective in patients with chronic migraine (14).…”
Section: Discussionmentioning
confidence: 99%